Functional status of platelets in type 2 diabetes patients showing no diabetic fundus changes (Ukrainian Journal of Ophthalmology, 2026)
Background: A search for informative indicators of diabetic retinopathy (DR) is important and should be linked to the investigation of potential causes of ocular microcirculation abnormalities.Purpose: To investigate the functional status of platelets in type 2 diabetes mellitus (DM2) patients showing no diabetic fundus changes.Materials and Methods: Thirty eight DM2 patients (38 eyes) manifesting no fundus changes were included in this case-control study. The ophthalmological examination included visual acuity assessment, non-contact tonometry, keratometry and refractometry, anterior eye slit lamp biomicroscopy, retinal wide-angle biomicroscopy, retinal optical coherence tomography and retinal photography. Platelets were isolated by centrifugation of patient’s citrated peripheral blood. The following agonists involved into physiological regulation of hemostasis were used: adenosine diphosphate (ADP; 5 ?m), adrenaline (5 ?m), angiotensin II (AN-II; 2 ?m), platelet activation factor (PAF, 150 ?m), and collagen (2 ?g/mL). Platelet aggregation was assessed spectrophotometrically with a Chrono-Log aggregometer.Results: Platelets were characterized by specific functional activities of GP VI receptors, ?2-adrenoreceptors, АТ1 purine receptors (P2Y12 and P2Y1 receptors) and PAF receptors. Hyperreactivity was a prevailing type of platelet response to agonists. Each type of receptor was characterized by a specific percentage platelet aggregation range related to the greatest share of patients under investigation: collagen, 80-90%; adrenaline, 75-80%; AN-II, 70-80%; ADP, 60-65% and PAF, 60-65%. If persistent, platelet hyperreactivity to one or more agonists can lead to thrombogenesis and ocular microcirculation abnormalities.Conclusion: The analysis of functional reactivity of platelets would provide insight into the clusters of functional activity of platelet receptors which are capable of maintaining the platelet proaggregation status and causing abnormalities in ocular microcirculation, and thus causing progression of DR. Further studies of platelets in vitro may be scientifically beneficial in permitting analysis of the development and progression of diabetic retinopathy.
Keywords: type 2 diabetes mellitus; functional status of platelets; diabetic retinopathy